2015
DOI: 10.1021/jacs.5b06809
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Electrodes for K-Ion Batteries

Abstract: We for the first time report electrochemical potassium insertion in graphite in a nonaqueous electrolyte, which can exhibit a high reversible capacity of 273 mAh/g. Ex situ XRD studies confirm that KC36, KC24, and KC8 sequentially form upon potassiation, whereas depotassiation recovers graphite through phase transformations in an opposite sequence. Graphite shows moderate rate capability and relatively fast capacity fading. To improve the performance of carbon K-ion anodes, we synthesized a nongraphitic soft c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

49
1,437
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,701 publications
(1,488 citation statements)
references
References 30 publications
49
1,437
0
2
Order By: Relevance
“…The positive computed E b for single-atom insertion might mean that higher states of charge are formed during potassiation, i.e., there is phase segregation. The same work found that amorphization significantly improves electrochemical performance, consistent with the calculation [75]. Specifically, the initial part of the voltage capacity curve was at about 1 V, consistent with Figure 3.…”
Section: Insertion Of LI Na K and Mg In Carbon: Effects Due To Ionsupporting
confidence: 82%
See 1 more Smart Citation
“…The positive computed E b for single-atom insertion might mean that higher states of charge are formed during potassiation, i.e., there is phase segregation. The same work found that amorphization significantly improves electrochemical performance, consistent with the calculation [75]. Specifically, the initial part of the voltage capacity curve was at about 1 V, consistent with Figure 3.…”
Section: Insertion Of LI Na K and Mg In Carbon: Effects Due To Ionsupporting
confidence: 82%
“…Our calculations also showed a significant magnitude of strengthening of insertion energy of Mg and K by amorphization [27], as is also shown in Figure 3, implying the possibility of electrochemical activity after amorphization. Graphite has been shown experimentally to work as an anode in K ion batteries [75]. The positive computed Eb for single-atom insertion might mean that higher states of charge are formed during potassiation, i.e., there is phase segregation.…”
Section: Insertion Of LI Na K and Mg In Carbon: Effects Due To Ionmentioning
confidence: 99%
“…5,23,24 Compared to soft carbon, graphite exhibits a more pronounced capacity fade and lower rate capability, but both deliver high capacities of about 260 mAh g −1 . 23 The use of HC is interesting as the capacity is mostly delivered above 0.1 V, which reduces the risk of K-metal plating. 24 Komaba et al demonstrated that in EC:DEC organic electrolytes KFSI [potassium bis(fluorosulfonyl)imide] is the most appropriate conductive salt in comparison with KClO 4 and KPF 6 due to its higher solubility.…”
mentioning
confidence: 99%
“…In addition, K-ion technology would benefit from the fact that graphite can be used on the anode side [3,4] (as in Li ion), which is not the case for Na ion and has seriously limited application of Na-ion technology.…”
mentioning
confidence: 99%